DIFFICULTIES FACED BY STUDENTS OF DIAN NUSWANTORO UNIVERSITY IN TRANSLATING COMIC - Rahmanti Asmarani (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2010)
Comic is the most favorable book for many people. Not only youth but also adult likes reading comic most, since it contains sequential art in the form of narrative. Recently many translated comic have been published. The aim of this study is to describe the evaluation of classical comic translation which was done by students of Translation Section. This paper also addresses the problems thatthe students found in translating comic. They were interviewed and asked to answer the questionnaires. The classroom observation during the project of comic translation was also conducted. The result of the data reveals that most of students faced the difficulties in translating comic, such as (intra) linguistic and extra linguistic problems. For (intra) linguistic, phrases, idiom and slang words are the problems that students got. One of the interesting result is the students are challenged to translate comic which is adjusted to Indonesian culture. They did not only learn how to translate comic well but also how to operate the computer in scanning and editing pictures.Keywords: comic, classical comic translation, intra linguistic, extralinguistic, Indonesian culture.